Evaluating the carbon footprint of the cork sector with a dynamic approach including biogenic carbon flows - Demertzi, Martha (2020)
Purpose The aim of the present study is to assess the influence of two different attributional life cycle assessment (LCA) approaches, namely static LCA (sLCA) and dynamic LCA (dLCA), through their application to the calculation of the carbon footprint (CF) of the entire cork sector in Portugal. The effect of including biogenic carbon sequestration and emissions is considered as well. Methods sLCA is often described as a static tool since all the emissions are accounted for as if occurring at the same time which may not be the case in reality for greenhouse gases. In contrast, dLCA aims to evaluate the impact of life cycle greenhouse gas emissions on radiative forcing considering the specific moment when these emissions occur. Results and discussion The results show that the total CF of the cork sector differs depending on the approach and time horizon chosen. However, the greater it is the time horizon chosen, the smaller the difference between the CF results of the two approaches. Additionally, the inclusion of biogenic carbon sequestration and emissions also influences significantly the CF result. The cork sector is considered a net carbon source when biogenic carbon is excluded from the calculations and a net carbon sink when biogenic carbon is included in the calculations since more carbon is sequestered than emitted along the sector. Conclusions dLCA allows an overview of greenhouse gas emissions along the time. This is an advantage as it allows to identify and plan different management approaches for the cork sector. Even though dLCA is a more realistic approach, it is a more time-consuming and complex approach for long life cycles. The choice of time horizon was found to be another important aspect for CF assessment.